Preparation method and application of sodium stearate modified medical stone-based adsorption material
Through the preparation method of modified Maifanshi-based adsorption materials, the problems of high economic cost of treating lead ions in water in the prior art, difficulty in material recycling and low adsorption efficiency are solved, and an efficient and economical lead ion removal effect is achieved, and a material suitable for recycling is provided.
Patent Information
- Application Number
- CN202510088200.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art has problems such as high economic costs, difficulty in recycling materials and low adsorption efficiency when treating lead ions in water, especially with fewer research and application of solid materials.
By using natural maifanite minerals as raw materials, sodium silicate, calcium carbonate and anthracite powder were added, and the maifanite-based adsorption material was prepared by ball milling, sieving, mixing and high-temperature calcining, and modified with sodium stearate surfactant to improve its adsorption performance.
The adsorption equilibrium measurement of modified maifanshi-based adsorbent materials is 5 times higher than that of unmodified materials. It can efficiently remove lead ions in water and exhibit excellent adsorption performance in various pH water environments. The material is stable and suitable for recycling.
Smart Images

Figure HDA0005250765170000011 
Figure HDA0005250765170000012 
Figure HDA0005250765170000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lead ion wastewater treatment, and specifically relates to a preparation method of a sodium stearate modified medical stone-based adsorption material and an application method thereof for removing lead ions in water. Background Art
[0002] Lead, as a heavy metal element with many excellent properties, is widely used in battery manufacturing, radiation protection, construction and pipelines, machinery manufacturing, chemical industry and other fields. In actual application, lead will be discharged into the environment in the form of waste gas, wastewater and waste residue. It is very easy to dissolve in aqueous solution and oxidize into lead ions, which will affect the aquatic environment. If the lead ions in water are not handled properly, the lead content in the human body will exceed the standard, which will cause many harms to the human body. Children who are in a lead-contaminated environment for a long time will have problems such as mental retardation, learning difficulties, and abnormal behavior because the brain will be affected by the synthesis and release of neurotransmitters due to lead interference. Excessive lead will also increase the burden on kidney and stomach function, inhibit the activity of heme synthase, and lead to anemia and immune system damage. It is urgent to find an economical, simple and efficient method to treat lead ions in water.
[0003] Nowadays, the methods for treating lead mainly include chemical precipitation, coagulation, membrane separation, adsorption, etc. The chemical precipitation method is simple in technology and easy to implement, but it requires further treatment, otherwise the precipitation of insoluble metal compounds produced by the reaction will cause secondary pollution. The coagulation method forms a colloid with impurity particles in the wastewater through a coagulant to achieve solid-liquid separation. Its effect is often affected by the type and dosage of the coagulant, and needs to be optimized according to the specific situation. Compared with other methods, the adsorption method has the advantages of high efficiency, simplicity, and good selectivity. It is one of the most effective methods for heavy metal wastewater treatment. Commonly used adsorbents include resins, chitosan, diatomaceous earth, bentonite, activated carbon, zeolite, etc. The prices of materials such as chitosan, activated carbon, and artificial zeolite are relatively expensive, and regeneration and recycling issues are the main problems limiting their application.
[0004] Most researchers focus on adsorption research on powdered adsorption materials, while research and application on solids are relatively rare. Solid materials have advantages in recycling and application, but their small specific surface area and adsorption saturation are still challenges. Solid materials can be further explored to optimize the structure and chemical properties of solid materials, improve adsorption performance and improve their efficiency in environmental management and resource recovery. Summary of the invention
[0005] The invention provides a new method for preparing a modified medical stone-based adsorption material, which is used to successfully adsorb and remove toxic lead ions in water. The invention uses natural medical stone mineral as a raw material, adds sodium silicate, calcium carbonate and anthracite powder to mix and prepare the medical stone-based adsorption material, and modifies the material with a sodium stearate surfactant. The whole preparation process is simple and convenient, and the invention is an innovative method with high economic benefits.
[0006] The technical solution adopted by the present invention is as follows:
[0007] A method for preparing a sodium stearate modified medical stone-based adsorption material, the specific steps are as follows:
[0008] (1) ball milling and sieving natural medical stone mineral to obtain medical stone powder;
[0009] (2) mixing medical stone powder and sodium sulfate solution, filtering and collecting the powder, washing with ultrapure water, drying the powder and grinding to obtain sodium sulfate-modified medical stone;
[0010] (3) adding calcium carbonate and anthracite powder to the sodium sulfate modified medical stone and mixing them evenly, adding alkaline sodium silicate solution dropwise to the mixture, stirring evenly to prepare a slurry;
[0011] (4) injecting the slurry into a pressure mold and pressing it into a cylinder, drying it at room temperature, calcining it, washing the excess alkaline sodium silicate to neutrality, and drying it at room temperature to obtain a medical stone-based adsorption material;
[0012] (5) The medical stone-based solid material is placed in a sodium stearate solution and heated and soaked, washed with ultrapure water until neutral, and dried to obtain a sodium stearate-modified medical stone-based adsorption material.
[0013] In step (1), the ball milling speed is 200-300 r / min, the ball milling time is 1-4 h, and the particle size of the medical stone powder is 100-200 meshes.
[0014] In step (2), the concentration of the sodium sulfate solution is 1-2 mol / L, the mass volume ratio of the medical stone powder and the sodium sulfate solution is 150-300 g:L, and the mixing time is 1-4 h to ensure uniform contact and prevent agglomeration from affecting the modification effect.
[0015] In step (2), the powder is dried at a temperature of 30-100° C. for 6-18 hours. The finer the powder particle size, the stronger the water retention and the longer the drying time required.
[0016] In step (3), the mass ratio of sodium sulfate modified medical stone, calcium carbonate and anthracite powder is 100:10:5-20.
[0017] In step (3), the concentration of alkaline sodium silicate is 0.2-1.5 mol / L, and the mass ratio of the mixture to the sodium silicate solution is 1:0.2-0.35.
[0018] In step (4), the calcination temperature is 500-800° C., the calcination time is 4-8 hours, and the drying time at room temperature is 6-18 hours.
[0019] The cylinder obtained after demoulding the pressure mold in step (4) has a height of 12 mm and a diameter of 13 mm.
[0020] In step (5), the concentration of sodium stearate solution is 0.05-0.2mol / L, and the mass volume ratio g:mL of medical stone-based adsorbent material to sodium stearate solution is 4-5g:100mL; the heating soaking temperature is 50-120°C, and the time is 1-4h. The higher the temperature, the higher the solubility of sodium stearate in aqueous solution, and the better the effect of modified medical stone; the ultrapure water washing temperature is 50-120°C.
[0021] The present invention also provides the use of the sodium stearate modified medical stone-based adsorption material prepared by the preparation method as an adsorbent to remove lead ions in water, which specifically comprises the following steps:
[0022] The pH value of the solution containing lead ions is controlled at 4-11, 40 mL of the lead ion solution of the required concentration is prepared and poured into a conical flask, the sodium stearate modified medical stone-based adsorption material is added into the conical flask and sealed, the conical flask is placed in an oscillator, after the oscillation time is over, the upper clear liquid is taken out to obtain a solution after the lead ions are removed, and the Pb in the solution containing lead ions is 2+ The concentration is 100-350 mg / L, and the additive is lead nitrate; the addition amount of the modified medical stone-based solid material is 2 g, and the maximum removal amount of lead ions by the modified medical stone-based adsorption material is 4.50576 mg / g.
[0023] Compared with the existing invention, the beneficial effects of the present invention are:
[0024] The invention uses natural medical stone mineral as the main raw material, prepares medical stone-based solid adsorption material by a simple and convenient preparation method, and modifies the medical stone-based solid adsorption material with a sodium stearate surfactant. The adsorption equilibrium amount of the modified medical stone-based solid material is increased by 5 times compared with that of unmodified lead, and shows excellent performance in removing lead ions, thereby providing a new idea and approach for solving the problem of lead ion pollution in the environment.
[0025] The invention improves the compression resistance of the modified medical stone-based adsorption material by high-temperature calcination, can be applicable to various water treatment environments, and can be very conveniently recycled. The modified medical stone-based adsorption material can be used as an adsorbent in various pH water environments, has the best adsorption effect when it is neutral, and has a strong removal ability for lead ions.
[0026] The invention uses cheap medical stone, calcium carbonate and anthracite powder to prepare a modified medical stone-based solid adsorption material, which has good stability and is a material for removing lead ions in polluted water economically and efficiently. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The XRD diagrams of the materials in Example 1 of the present invention are as follows;
[0028] Figure 2 This is a graph showing the change in removal rate of the medical stone-based adsorption material at different pH values before and after modification obtained in Example 1 of the present invention;
[0029] Figure 3 Graph showing the removal rate and adsorption amount of the medical stone-based adsorption material before and after modification at different initial lead ion concentrations obtained in Example 1 of the present invention;
[0030] Figure 4 This is the SEM image of each material in Example 1 of the present invention;
[0031] Figure 5 The infrared spectra of medical stone, medical stone modified with sodium sulfate, medical stone-based adsorption material, medical stone-based adsorption material modified with sodium stearate, and medical stone-based adsorption material with sodium stearate;
[0032] Figure 6 The XPS full spectrum of sodium stearate modified medical stone-based adsorbent material and sodium stearate modified medical stone-based adsorbent material after adsorbing lead ions and the characteristic peaks of each element;
[0033] Figure 7 A schematic diagram of an adsorption device for an adsorption-desorption cycle of a sodium stearate-modified medical stone-based adsorption material;
[0034] Figure 8 The removal rate of lead ions by sodium stearate-modified medical stone-based adsorbent material after adsorption-desorption cycles. DETAILED DESCRIPTION
[0035] In order to more clearly illustrate the technical solution and application means of the present invention, the present invention will be briefly introduced below in conjunction with specific embodiments and drawings.
[0036] The medical stone, calcium carbonate, anthracite powder, sodium sulfate and sodium stearate etc. used in the embodiments of the present invention are all conventional commercial products; wherein the chemical composition of the medical stone is SiO2: 66.22%, Al2O3: 16.00%, Fe2O3: 1.23%, FeO: 1.04%, MgO: 1.58%, CaO: 2.34%, K2O: 3.12%, Na2O: 6.02%, TiO2: 0.32%, P2O5: 0.18%, MnO: 0.05%, and the others are inevitable impurities; calcium carbonate, sodium stearate and sodium sulfate are all analytically pure and purchased from Shanghai Yansu Technology Co., Ltd.; anthracite powder is purchased online; in the embodiments, the lead ion solution is obtained by adding water to lead nitrate, and the pH value is adjusted by using 0.1mol / L dilute hydrochloric acid and 0.1mol / L sodium hydroxide solution.
[0037] Example 1
[0038] A method for preparing a sodium stearate modified medical stone-based adsorption material, the specific steps are as follows:
[0039] (1) using a ball mill to ball-mill natural medical stone mineral at a speed of 200 r / min for 2 h, and obtaining medical stone powder of 100-200 mesh after sieving;
[0040] (2) 200 g of medical stone powder and 1 L of 1 mol / L sodium sulfate solution were mixed for 1 h, the mixture was filtered, the resulting powder was collected, and the powder was washed with ultrapure water 3 times to wash away the excess sodium sulfate solution on the surface;
[0041] (3) drying the powder of step (2) at 55° C. for 12 h, and grinding to obtain sodium sulfate-modified medical stone;
[0042] (4) according to the mass ratio of sodium sulfate modified medical stone, calcium carbonate and anthracite powder of 100:10:15, the ground sodium sulfate modified medical stone, calcium carbonate and anthracite powder are uniformly mixed, and according to the mass ratio of the mixture to the sodium silicate solution of 1:0.2, an alkaline sodium silicate solution with a concentration of 0.5 mol / L is added dropwise to the mixture, and stirred to prepare a slurry;
[0043] (5) injecting the slurry of step (4) into a pressure mold, pressing into a cylinder with a height of 12 mm and a diameter of 13 mm, drying at room temperature for 12 h, and then heat-preserving at a calcination temperature of 700° C. for 5 h to form, washing the calcined cylinder to neutrality, removing excess alkaline sodium silicate, and drying at room temperature for 12 h to obtain a medical stone-based adsorption material;
[0044] (6) 4 g of the medical stone-based adsorbent material of step (5) was placed in 100 mL of a 0.1 mol / L sodium stearate solution at 85° C., mixed evenly and soaked for 2 h. After the mixture was washed with 85° C. ultrapure water until the solid was neutral, and the unbound sodium stearate surfactant was removed from the modified medical stone-based adsorbent material, and dried to obtain the sodium stearate-modified medical stone-based adsorbent material.
[0045] Figure 1 It is the XRD diagram of the material of Example 1 of the present invention. The natural medical stone mineral is a triclinic system, and the main components are quartz and sodium feldspar. After sodium sulfate modification, the peak area of the sodium sulfate modified medical stone decreases, indicating that the crystallinity has increased after the modification. After introducing the calcium element, the diffraction peak intensity of sodium feldspar in the medical stone-based adsorption material increases, and the diffraction peak of sodium feldspar decreases. After calcination, impurities reduce the crystallinity and further increase. After the modification, the medical stone-based adsorption material does not destroy the original crystal structure of the medical stone, and will not affect the original physical properties of the medical stone.
[0046] Prepare multiple portions of 40 mL of a 200 mg / L lead ion solution and pour them into a conical flask, adjust the pH of the lead ion solution to 4, 5, 6, 7, 8, 9, 10, and 11, respectively, take 2 g of the medical stone-based adsorption material prepared in step (5) of Example 1 and the modified medical stone-based adsorption material prepared in step (6), add them to the lead ion solutions in different conical flasks with the same pH value, seal them, put the conical flasks into an oscillator, and after oscillating for 2 hours, take out the supernatant to obtain a solution after the lead ions are removed.
[0047] Figure 2 The figure shows the removal rate variation of the medical stone-based adsorption material (MFS) prepared in step (5) of Example 1 and the modified medical stone-based adsorption material (SSMFS) prepared in step (6) at different pH values. It can be seen from the figure that pH has a great influence on the adsorption performance of the adsorption material. When the pH value is 8, the modified medical stone-based adsorption material has the highest removal rate of lead ions in water. The medical stone-based adsorption material before modification is slightly better in an acidic environment than in an alkaline environment. In an alkaline environment, the adsorption effect of the modified medical stone-based adsorption material is better than that in an acidic environment.
[0048] Prepare multiple 40mL portions of lead ion solutions with concentrations of 100mg / L, 150mg / L, 250mg / L, 300mg / L, and 350mg / L, respectively; take 2g of the medical stone-based adsorbent material prepared in step (5) of Example 1 and the modified medical stone-based adsorbent material prepared in step (6), add them to the lead ion solutions of the same concentration in different conical flasks, seal them, put the conical flasks into an oscillator, and after oscillating for 2h, take out the supernatant to obtain a solution after the lead ions are removed.
[0049] Figure 3The figure shows the removal rate and adsorption capacity of the medical stone-based adsorbent (MFS) before modification and the modified medical stone-based adsorbent (SSMFS) obtained after modification with sodium stearate as adsorbents at different initial lead ion concentrations. As the initial lead ion concentration increases from 100 mg / L to 350 mg / L, the removal rate of lead ions of the modified medical stone-based adsorbent obtained after sodium stearate modification decreases, and the equilibrium adsorption capacity gradually increases. When the initial lead ion concentration of the modified medical stone-based adsorbent is 200 mg / L, the removal rate of lead ions reaches 99.129%, and the rate of increase in the equilibrium adsorption capacity begins to decrease. Under the same conditions for MFS and SSMFS, the adsorption equilibrium capacity of SSMFS obtained after SS modification is 5 times higher than that of MFS.
[0050] Figure 4 SEM and EDS images of the material. Figure 4 (a) is a medical stone-based adsorption material, Figure 4 (b) is a sodium stearate modified medical stone based adsorption material, Figure 4 (c) and 4 (d) are SEM images and EDS detection images of sodium stearate modified medical stone-based adsorbent material (SSMFS) after adsorption experiment at pH = 8 and lead ion concentration of 200 mg / L. Figure 4 (a) It can be seen that after the medical stone-based adsorption material was calcined with the addition of pore-forming agent coal powder, the surface of the medical stone was relatively rough. The carbon dioxide gas released after calcination volatilized and the coal powder was carbonized to produce a network structure with more pores. Figure 4 (b) It can be seen that the surface of the medical stone modified with sodium stearate is densely distributed with sodium stearate spheres. Figure 4 (c) and (d) show that after SSMFS adsorbs lead ions, a layered structure containing lead elements appears. The lead ions, stearate ions and OH in water - The ions undergo complexation reaction to obtain a lead complex.
[0051] Figure 5 The infrared spectra of medical stone, medical stone modified with sodium sulfate, medical stone-based adsorption material, medical stone-based adsorption material modified with sodium stearate and medical stone-based adsorption material with sodium stearate after adsorption of lead ions are shown in the figure. -1 and 761cm -1 There is a significant Si-O asymmetric peak stretching vibration at 693cm -1 There is a symmetrical peak of Si-O-Si stretching vibration at 535cm -1 The most obvious vibration is the deformation vibration of Si-O bond in the silicon-oxygen tetrahedron of medical stone, at 646 cm -1 It is the stretching vibration of O-Al-O bond at 590cm -1 The stretching vibration peak of Fe-O is at 500-900cm-1 The characteristic peaks of the medical stone are numerous and complex, because there are many interactions between the infrared absorption peaks of chemical bonds of different metal elements; the peak of sodium sulfate modified medical stone is 762cm -1 、694cm -1 and 536cm -1 The characteristic peak at 724cm-1 was red-shifted, indicating that the sodium sulfate solution had an effect on the Si-O chemical bond vibration of medical stone; the medical stone-based adsorption material was calcined after adding calcium carbonate and pore-forming agent. -1 There is a significant vibration between calcium ions and oxygen atoms at 1450cm -1 The characteristic peak of carbonate is enhanced at 2917.89cm -1 and 2850.17cm -1 The methyl and methylene stretching vibration peaks appeared at 1540 cm -1 and 1577cm -1 The C=O of sodium stearate appeared, indicating that sodium stearate was successfully loaded on the medical stone-based adsorption material (MFS) before modification. The sodium stearate medical stone-based adsorption material adsorbed lead ions at 3438 cm at pH 8 and lead ion concentration of 200 mg / L. -1 The characteristic peak is the OH bond, and the OH bond intensity becomes lower and red-shifted, mainly due to the OH - ions and lead ions undergo surface complexation.
[0052] Figure 6 (a) is the full XPS spectrum of sodium stearate modified medical stone-based adsorbent (SSMFS) and sodium stearate modified medical stone-based adsorbent (SSMFS-Pb) after adsorbing lead ions. It can be seen that SSMFS mainly contains C, O, Si, Fe, Al and Ca elements. Ca is mainly CaCO3 introduced during the synthesis of SSMFS. The characteristic peak of Pb appears after SSMFS adsorbs lead ions. Figure 6 (b) is the C1sXPS spectra of SSMFS and SSMFS after adsorption of lead ions. The CC peak of 284.79 eV was used for spectral line correction. The peaks at 285.5 eV, 288.1 eV and 284.3 eV are CO, OC=O and CH respectively. This is because the modification of sodium stearate introduces CH3, CH2 and OC=O. After SSMFS adsorbs lead ions, the peaks of CO, OC=O and CH shift to the left by 0.1 eV, which may be the result of the complexation between the surface sodium stearate and the lead ions. Figure 6(c) is the O1sXPS spectra of SSMFS and SSMFS after adsorbing lead ions. The peaks at 531.3eV, 532.3eV, 530.6eV and 533.6eV are OH-, C=O / CO, Al2O3 / SiO2 and H2O, respectively. The binding energy of OH- and C=O / CO increased by 0.3eV, and the binding energy of H2O increased by 0.4eV. After SSMFS adsorbed lead ions, the binding energy of Pb-O appeared at 528.72eV, indicating that the combination of lead ions and oxygen ions is the reason for the removal of lead ions by SSMFS. Figure 6 (d) is the Al2p XPS spectra of SSMFS and SSMFS after adsorption of lead ions. The peak at 73.67 eV is the electron binding energy of Al2O3 in silicate. After SSMFS adsorbs lead ions, a peak of Al(OH)3 is generated at 74.50 eV, indicating that the presence of lead ions promotes the reaction of aluminum atoms in aqueous solution. Figure 6 (e) is the Ca2p XPS spectra of SSMFS and SSMFS after adsorption of lead ions. After SSMFS adsorbs lead ions, the binding energy of Ca-OH, CaCO3 and CaO increases, indicating that the presence of stearate affects the binding energy of calcium ions and oxygen atoms; Figure 6 (f) is the XPS spectra of Fe2p after SSMFS and SSMFS adsorbed lead ions. Due to the low content of iron in SSMFS, the peak intensities of FeOOH and Fe2O3 are low. During the adsorption of lead ions, the reaction between iron ions and oxygen atoms intensifies, and the peak intensities of FeOOH and Fe2O3 decrease. Figure 6 (g) is the XPS spectra of Pb4f after SSMFS and SSMFS adsorbed lead ions. The peaks at 138.8 eV, 138.2 eV and 143.1 eV are Pb-O, Pb(OH)2 and Pb 2+ 4f 5 / 2 , prove that Pb 2+ It has been successfully adsorbed on SSMFS, indicating that oxygen sites and hydroxyl groups are the main complexation sites in this process; Figure 6 (h) is the XPS spectrum of Si2p after SSMFS and SSMFS adsorbed lead ions. The peaks at 102.5eV, 104.6eV, 99.5eV and 101.3eV are Silicates / Si-O, Si-OH, Si-OX and Si-OM, respectively. The binding energy of Silicates / Si-O and Si-OX decreased by 0.3eV. The complex generated by the cations affected the arrangement of the Si-O bonds in the matrix.
[0053] Prepare 600 mL of 200 mg / L lead ion solution and pour into Figure 7The homemade cyclic adsorption device shown in the figure was set with a flow rate of 0.1 m / s, 12 SSMFS were placed in a water pipe, the temperature was 25°C, the cyclic adsorption time was 2 h, the upper clear liquid was taken out to obtain the solution after the lead ions were removed, and the absorbance of the lead ion solution was measured at a wavelength of 575 nm using an ultraviolet spectrophotometer to obtain the removal rate. 2 g of the adsorbed SSMFS was soaked in 50 mL of a 0.1 mol / L NaOH solution for 200 min for desorption, and washed with ultrapure water for multiple times until neutral. The desorbed SSMFS was dried at 50°C for 2 h and then reused, and the cyclic adsorption-desorption experiment was carried out 5 times.
[0054] Figure 8 The removal rate of lead ions after five adsorption-desorption cycles of sodium stearate modified medical stone-based adsorbent material (SSMFS) is the highest for the first time, which is 99.129%. As the number of cycles increases, desorption is carried out again after each adsorption, and it is found that the stability decreases and the removal rate decreases. After the fifth time, the removal rate drops to 58.16%. The main reason is that SSMFS has strong curing property. SSMFS forms a stable complex after adsorbing lead ions by ion exchange and surface complex reaction. The water-containing amorphous material in medical stone is further utilized to highly crystallize and solidify lead ions, resulting in a reduction in the analytical effect. Another reason is that stearic acid ions are lost after multiple adsorption-analysis, and the site for combining lead ions by surface complex reaction is reduced, resulting in a decrease in adsorption performance. However, the stability is good after five cycles of adsorption-desorption, and the removal rate of lead ions is still maintained at about 60%, indicating that what Example 1 prepares is a material that removes lead ions in contaminated water economically and efficiently.
[0055] Example 2
[0056] A method for preparing a sodium stearate modified medical stone-based adsorption material, the specific steps are as follows:
[0057] (1) using a ball mill to grind natural medical stone mineral for 4 h at a speed of 250 r / min, and obtaining medical stone powder of 100-200 mesh after sieving;
[0058] (2) 150 g of medical stone powder and 1 L of 1.5 mol / L sodium sulfate solution were mixed for 2 h, the mixture was filtered, the resulting powder was collected, and the powder was washed three times with ultrapure water to wash away excess sodium sulfate solution on the surface;
[0059] (3) drying the powder of step (2) at 30° C. for 18 h, and grinding to obtain sodium sulfate-modified medical stone;
[0060] (4) according to the mass ratio of sodium sulfate modified medical stone, calcium carbonate and anthracite powder of 100:10:5, the ground sodium sulfate modified medical stone, calcium carbonate and anthracite powder are evenly mixed, and according to the mass ratio of the mixture to the sodium silicate solution of 1:0.35, 1.5 mol / L alkaline sodium silicate solution is dropwise added to the mixture, and stirred to prepare a slurry;
[0061] (5) injecting the slurry of step (4) into a pressure mold and pressing it into a cylinder with a height of 12 mm and a diameter of 13 mm, drying it at room temperature for 12 hours, and then calcining it at 800° C. for 4 hours to form it, washing the calcined cylinder to neutrality, removing excess alkaline sodium silicate, and drying it at room temperature for 18 hours to obtain a medical stone-based adsorption material;
[0062] (6) Take 5 g of the medical stone-based adsorbent material of step (5) and put it into 100 mL of a 0.2 mol / L sodium stearate solution at 120° C., mix evenly and soak for 4 h. After the end, wash the solid with 120° C. ultrapure water until it is neutral, remove the unbound sodium stearate surfactant from the modified medical stone-based adsorbent, and dry to obtain the sodium stearate modified medical stone-based adsorbent.
[0063] Example 3
[0064] A method for preparing a sodium stearate modified medical stone-based adsorption material, the specific steps are as follows:
[0065] (1) using a ball mill to ball-mill natural medical stone mineral at a speed of 300 r / min for 1.5 h, and obtaining medical stone powder of 100-200 mesh after sieving;
[0066] (2) 300 g of medical stone powder and 1 L of 2 mol / L sodium sulfate solution were mixed for 4 h, the mixture was filtered, the resulting powder was collected, and the powder was washed with ultrapure water 3 times to wash away the excess sodium sulfate solution on the surface;
[0067] (3) drying the powder of step (2) at 100° C. for 6 h, and grinding to obtain sodium sulfate-modified medical stone;
[0068] (4) according to the mass ratio of sodium sulfate modified medical stone, calcium carbonate and anthracite powder of 100:10:10, the ground sodium sulfate modified medical stone, calcium carbonate and anthracite powder are mixed uniformly, and according to the mass ratio of the mixture to the sodium silicate solution of 1:0.3, 0.2 mol / L alkaline sodium silicate solution is added dropwise to the mixture, and stirred uniformly to prepare a slurry;
[0069] (5) injecting the slurry of step (4) into a pressure mold and pressing it into a cylinder with a height of 12 mm and a diameter of 13 mm, drying it at room temperature for 12 hours, and then heat-preserving it at a calcination temperature of 500° C. for 8 hours to form it, washing the calcined cylinder to neutrality, removing excess alkaline sodium silicate, and drying it at room temperature for 9 hours to obtain a medical stone-based adsorption material;
[0070] (6) 4.5 g of the medical stone-based adsorbent material of step (5) was placed in 100 mL of a 0.05 mol / L sodium stearate solution at 50° C., mixed evenly and soaked for 3 h. After the mixture was washed with 50° C. ultrapure water until the solid was neutral, and the unbound sodium stearate surfactant was removed from the modified medical stone-based adsorbent material, and dried to obtain the sodium stearate-modified medical stone-based adsorbent material.
[0071] Example 4
[0072] A method for preparing a sodium stearate modified medical stone-based adsorption material, the specific steps are as follows:
[0073] (1) using a ball mill to grind natural medical stone mineral at a speed of 300 r / min for 1 h, and obtaining medical stone powder of 100-200 mesh after sieving;
[0074] (2) 250 g of medical stone powder and 1 L of 1.5 mol / L sodium sulfate solution were mixed for 3 h, the mixture was filtered, the resulting powder was collected, and the powder was washed with ultrapure water 3 times to wash away the excess sodium sulfate solution on the surface;
[0075] (3) drying the powder of step (2) at 80° C. for 12 h, and grinding to obtain sodium sulfate-modified medical stone;
[0076] (4) according to the mass ratio of sodium sulfate modified medical stone, calcium carbonate and anthracite powder of 100:10:20, the ground sodium sulfate modified medical stone, calcium carbonate and anthracite powder are mixed uniformly, and according to the mass ratio of the mixture to the sodium silicate solution of 1:0.25, 1 mol / L alkaline sodium silicate solution is added dropwise to the mixture, and stirred uniformly to prepare a slurry;
[0077] (5) injecting the slurry of step (4) into a pressure mold and pressing it into a cylinder with a height of 12 mm and a diameter of 13 mm, drying it at room temperature for 12 hours, and then calcining it at 600° C. for 7 hours to form it, washing the calcined cylinder to neutrality, removing excess alkaline sodium silicate, and drying it at room temperature for 6 hours to obtain a medical stone-based adsorption material;
[0078] (6) 4 g of the medical stone-based adsorbent material of step (5) was placed in 100 mL of a 0.15 mol / L sodium stearate solution at 100° C., mixed evenly, and soaked for 1 h. After the mixture was washed with 100° C. ultrapure water until the solid was neutral, and the unbound sodium stearate surfactant was removed from the modified medical stone-based adsorbent material, and dried to obtain the sodium stearate-modified medical stone-based adsorbent material.
[0079] The specific implementation modes of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.
Claims
1. A method for preparing a sodium stearate modified medical stone-based adsorption material, characterized in that: The specific steps are as follows: (1) ball-milling and sieving natural medical stone mineral to obtain medical stone powder; (2) mixing medical stone powder and sodium sulfate solution, filtering and collecting the powder, washing with ultrapure water, drying the powder and grinding to obtain sodium sulfate-modified medical stone; (3) adding calcium carbonate and anthracite powder to the sodium sulfate modified medical stone and mixing them evenly, adding sodium silicate solution dropwise to the mixture, stirring evenly to prepare a slurry; (4) the slurry is injected into a mold and pressed into a cylinder, dried at room temperature and then calcined into a shape, washed to neutrality, and dried at room temperature to obtain a medical stone-based adsorption material; (5) The medical stone-based adsorbent material is placed in a sodium stearate solution and heated and soaked, washed with ultrapure water until neutral, and dried to obtain a sodium stearate-modified medical stone-based adsorbent material.
2. The method for preparing the sodium stearate modified medical stone-based adsorbent material according to claim 1, characterized in that: In step (1), the ball milling speed is 200-300 r / min, the ball milling time is 1-4 h, and the particle size of the medical stone powder is 100-200 meshes.
3. The method for preparing the sodium stearate modified medical stone-based adsorbent material according to claim 1, characterized in that: In step (2), the concentration of the sodium sulfate solution is 1-2 mol / L, the mass volume ratio of the medical stone powder and the sodium sulfate solution is 150-300 g:1 L, and the mixing time is 1-4 h.
4. The method for preparing the sodium stearate modified medical stone-based adsorbent material according to claim 1, characterized in that: In step (2), the powder is dried at 30-100° C. for 6-18 hours.
5. The method for preparing the sodium stearate modified medical stone-based adsorbent material according to claim 1, characterized in that: In step (3), the mass ratio of sodium sulfate modified medical stone, calcium carbonate and anthracite powder is 100:10:5-20.
6. The method for preparing the sodium stearate modified medical stone-based adsorbent material according to claim 1, characterized in that: The concentration of the sodium silicate solution in step (3) is 0.2-1.5 mol / L, and the mass ratio of the mixture to the sodium silicate solution is 1:0.2-0.
35.
7. The method for preparing the sodium stearate modified medical stone-based adsorbent material according to claim 1, characterized in that: In step (4), the calcination temperature is 500-800° C., the calcination time is 4-8 hours, and the drying time at room temperature is 6-18 hours.
8. The method for preparing the sodium stearate modified medical stone-based adsorbent material according to claim 1, characterized in that: In step (5), the concentration of the sodium stearate solution is 0.05-0.2 mol / L, the mass volume ratio of the medical stone-based adsorption material to the sodium stearate solution is 4-5 g:100 mL; the heating and soaking temperature is 50-120° C., and the time is 1-4 h.
9. The method for preparing the sodium stearate modified medical stone-based adsorbent material according to claim 1, characterized in that: The ultrapure water washing temperature in step (5) is 50-120°C.
10. Use of the sodium stearate modified medical stone-based adsorption material prepared by the preparation method according to claim 1 for removing lead ions from water.
Citation Information
Patent Citations
Composite ionic adsorption material and preparation method thereof
CN103071453A
Preparation method and application of adsorbent for treating lead-containing waste water
CN104437389A
Environmental heavy metal pollution repairing agent as well as preparation method and application thereof
CN114749141A